Periostin Promotes the Proliferation, Differentiation and Mineralization of Osteoblasts from Ovariectomized Rats - Yan, Jun; Wang, Zidong; Xian, Li; Wang, Dawei; Chen, Yunzhen; Bai, Jie; Liu, Hai-juan (Hormone and Metabolic Research, 2024)
Perimenopausal period causes a significant amount of bone loss, which results in primary osteoporosis (OP). The Periostin (Postn) may play important roles in the pathogenesis of OP after ovariectomized (OVX) rats. To identify the roles of Postn in the bone marrow mesenchymal stem cell derived osteoblasts (BMSC-OB) in OVX rats, we investigated the expression of Wnt/β-catenin signaling pathways in BMSC-OB and the effects of Postn on bone formation by development of BMSC-OB cultures. Twenty-four female Sprague–Dawley rats at 6 months were randomized into 3 groups: sham-operated (SHAM) group, OVX group and OVX+Postn group. The rats were killed after 3 months, and their bilateral femora and tibiae were collected for BMSC-OB culture, Micro-CT Analysis, Bone Histomorphometric Measurement, Transmission Electron Microscopy and Immunohistochemistry Staining. The dose/time-dependent effects of Postn on the proliferation, differentiation and mineralization of BMSC-OB and the expression of osteoblastic markers were measured in in vitro experiments. We found increased Postn increased bone mass, promoted bone formation of trabeculae, Wnt signaling and the osteogenic activity in osteoblasts in sublesional femur. Postn have the function to enhance cell proliferation, differentiation and mineralization at a proper concentration and incubation time. Interestingly, in BMSC-OB from OVX rats treated with the different dose of Postn, the osteoblastic markers expression and Wnt/β-catenin signaling pathways were significantly promoted. The direct effect of Postn may lead to inhibit excessive bone resorption and increase bone formation through the Wnt/β-catenin signaling pathways after OVX. Postn may play a very important role in the pathogenesis of OP after OVX.
Keywords: osteoporosis; periostin; osteoblast